Whither Risk Assessment: New Challenges and Opportunities a Third of a Century After the Red Book. Issue 11 (23rd November 2015) - Greenberg, Michael; Goldstein, Bernard D.; Anderson, Elizabeth; Dourson, Michael; Landis, Wayne; North, D. Warner
Abstract : Six multi‐decade‐long members of SRA reflect on the 1983 Red Book in order to examine the evolving relationship between risk assessment and risk management; the diffusion of risk assessment practice to risk areas such as homeland security and transportation; the quality of chemical risk databases; challenges from other groups to elements at the core of risk assessment practice; and our collective efforts to communicate risk assessment to a diverse set of critical groups that do not understand risk, risk assessment, or many other risk‐related issues. The authors reflect on the 10 recommendations in the Red Book and present several pressing challenges for risk assessment practitioners.